EKSISTENSI KENDURI NANGAL DALAM MASYARAKAT GAYO LOKOP SERBAJADI KABUPATEN ACEH TIMUR - madhan anis; Subandi Subandi (Program Studi Pendidikan Sejarah - Universitas Samudra, 2019)
Kenduri Nangal is a traditional ceremony of the Gayo Lokop community before returning down to the fields. Nangal, is one of the local wisdoms of Hablumminnallah and Hablumminannas which is carried out by the Gayo Lokop Serbajadi community in East Aceh Regency each time they will start planting rice simultaneously. Berume Resam (rice planting season), a kind of ritual carried out from generation to generation, is filled with prayers together, asking the Almighty to be given facilities and to be kept away from disasters until the harvest time. Kendal Nangal which has noble values and cultural wisdom that are the hallmark of the Gayo Lokop Serbajadi community.